Financial Sector Assessment : Lebanon - World Bank; International Monetary Fund (World Bank, Washington, DC, 2017)
Lebanon has maintained financial stability through repeated shocks and challenges for the last quarter century. Over time, macroeconomic and financial vulnerabilities have accumulated. Government debt and deposits at the Banque du Liban (BdL) account for close to half of aggregate bank assets and almost all banks have similar business models and risk profiles. Central bank policies help mitigate risks and maintain confidence. The banking system has proven resilient to domestic shocks and regional turmoil. Effective oversight and crisis management have underpinned stability. The banking sector is, directly and indirectly (through collateral), exposed to real estate. The housing segment has weakened, with declining prices in some market segments. Due to structural constraints, Lebanese capital markets remain under-developed. Certain improvements are still needed on the regulatory and supervisory front, including: (i) the creation of the Sanctioning Committee and Capital Markets Tribunal, (ii) implementation of a package of CMA regulations, (iii) enhancing the supervision of Mid clear, and (iv) cooperation with the Insurance Control Commission (ICC) to foster a growing and soundly regulated insurance and pension fund industry. In terms of access to finance, Lebanon stands above regional peers, but below upper middle income countries. Despite progress, access to finance for small and medium enterprises (SMEs) has still room for improvement. The micro finance industry plays an important role in financial inclusion and, while it does not represent a systemic risk, a well-calibrated regulatory requirement should be imposed to the main players. More can be done to foster financial inclusion within the strict anti-money laundering and terrorism financing regulatory framework.